INTRODUCING THE EFFECTS OF SMOKING ON THE HEART AND BLOOD VESSELS TO REDUCE SMOKING BEHAVIOR AMONG STUDENTS - Firdaus , Abraham Ahmad Ali; Riza , Mochamad Faishal; Raharjeng, Sa'bania Hari; Sulistyorini; Agnovianto, Yuriske (Community Service Journal of Indonesia, 2024)
Smoking causes various diseases in our bodies, such as heart disease and blood vessel disorders, lung cancer, oral cavity cancer, laryngeal cancer, high blood pressure, impotence as well as pregnancy disorders and fetal defects. The dangers of smoking are not only aimed at smokers (active smokers) but also for non-smokers who inhale cigarette smoke around smokers (passive smokers) and in fact the effects received from passive smokers will be much more dangerous than active smokers. Because of the many negative impacts that arise for teenage smokers, it is necessary to provide knowledge and understanding to teenagers, especially Islamic boarding school children, regarding the dangers posed by smoking. The goal is to increase understanding by providing education to Students regarding the effects of smoking on the heart and blood vessels as an effort to reduce smoking behavior among students in PP. Al Hikam Bangkalan. The methods used in counseling are lectures and questions answer. Before counseling, participants were given a pre-test, then after counseling, participants were given a post-test. The results of the pre-test and post-test are assessed and then data processing and evaluation are carried out. Pre-test results and post-test regarding knowledge of the effects of smoking on the heart and blood vessels through a questionnaire, there was a direct increase in scores by students who took part in this activity. The percentage increase in average value was 9.7%. This significant increase in the average value indicates a change in the level of knowledge of the participants after attending the counseling session. Introducing the effects of smoking on the heart and blood vessels as an effort to reduce smoking behavior among students in PP. Al Hikam Bangkalan has increased knowledge and understanding of the dangers of smoking.